IMPLANTOLOGY – A PROMISING DIRECTION IN MODERN DENTISTRY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article provides a comprehensive scientific analysis of implantology as one of the most important and rapidly developing fields of modern dentistry. The study examines the historical development of dental implantation, its biological and biomechanical principles, and the essence of the osseointegration process. Special attention is paid to modern implant materials, their biocompatibility, and the role of digital technologies such as CBCT, CAD/CAM systems, and 3D planning in improving clinical outcomes. The effectiveness, advantages, potential risks, and long-term success rates of dental implants are evaluated based on current scientific literature. The findings highlight the strategic importance of implantology in oral rehabilitation and its future development prospects.